قلق الامتحان و علاقته بالتحصيل الدراسي لدى تلاميذ السنة الثالثة ثانوي - صحراوي، نسرين (جامعة الوادي university of Eloued, 2019)
ملخص: تهدف هذه الدراسة إلى معرفة العلاقة بين قلق الامتحان والتحصيل الدراسي لدى تلاميذ ثالثة ثانوي ، كما تهدف إلى معرفة الفروق بين قلق الامتحان والتحصيل الدراسي وذلك بالنسبة إلى :الجنس، الشعبة الدراسية. وفي هذه الدراسة تم استخدام المنهج الوصفي الارتباطي، لملائمته مع طبيعة دراستنا الحالية، وقد اختيرت العينة بالطريقة القصدية من تلاميذ وتلميذات سنة ثالثة ثانوي من ثانويتين ( حفيان محمد العيد ، صنديد محمد منيب) بكونيين. أما فيما يتعلق بأداة الدراسة فكانت عبارة عن استبيان قلق الامتحان من إعداد (دكتور: غربي عبد الناصر)، وبإضافة إلى نتائج ومعدلات التلاميذ ، وبعد التأكد من الخصائص السيكو مترية للأداة ومدى ملائمتها للغرض الذي وضعت لأجله، تم تطبيقهما على عينة مكونة من 90 تلميذا وتلميذة من سنة ثالثة ثانوي، وقد تم الاعتماد في هذه الدراسة على الحزمة الإحصائية للعلوم الاجتماعية(spss)، النسخة رقم25 بحيث استخدم في التحليل: معامل ارتباط بيرسون، معامل سيبرمان، جيتمان، معامل ألفا كرو نباخ، المتوسط الحسابي، الانحراف المعياري ، اختبار( ت) ، معامل Anovaليتم التوصل إلى النتائج التالية: لا توجد علاقة ذات دلالة إحصائية بين قلق الامتحان والتحصيل الدراسي لدى تلاميذ ثالثة ثانوي. لا توجد فروق ذات دلالة إحصائية في قلق الامتحان تعزى لمتغير الجنس. لا توجد فروق ذات دلالة إحصائية في قلق الامتحان تعزى لمتغير الشعبة. لا توجد فروق ذات دلالة إحصائية في التحصيل الدراسي تعزى لمتغير الجنس. لا توجد فروق ذات دلالة إحصائية في التحصيل الدراسي تعزى لمتغير الشعبة. ومن هنا نستنتج أنه لا توجد علاقة بين قلق الامتحان والتحصيل الدراسي لدى تلاميذ ثالثة ثانوي، ولا توجد فروق ذات دلالة إحصائية بين المتغيرات(الجنس ،الشعبة).. Summary : This study aims to identifying the relationship between exam pressure and scholar achievement for high school third year students, and also recognizing the differences .of this relationship according to gender and branch study variances. And in this study, the descriptive correlative approach has been used, because it fits the nature of our current study. The sample was chosen willingly from 3rd year pupils of the two high schools in Kouinine: Hafiene Mohammed Laid and Sendid Mohammed Mounib. Concerning the study tool, it was a printed questionnaire made by Dr. Gharbi Abdennacer, additionally the results and rates of pupils. After verifying the tool’s psychometric features and how good does it fit the goal, they were applied on a sample of 90 pupils of different genders and branches. This study was based on the Statistical Package for Social Sciences (SPSS) version 25 , more specifically: Pearson Correlation, Silberman coefficient, Jitman, alpha-kern bach Coefficient, Arithmetic Average, standard deviation, T exam and Anova Coefficient were used to reach the following results: 1. There was no statistical indication relationship between test pressure and scholar attainment among secondary school pupils. 2. There were no statistical indication differences in exam anxiety due to sex variable. 3. There were no statistical indication differences in exam anxiety due to the branch variances. 4. There were no statistical indication differences in educational attainment due to gender variable. 5. There were no statistically significant differences in scholar achievement due to the variable of the branch. From here we can conclude that there was no relationship between exam pressure and scholar achievement for third high school pupils. There were no statistical indication differences between the variables (gender, branch).
مذكرة ماستر في علم النفس تخصص علم النفس المدرسي
Keywords: قلق الإمتحان، التحصيل الدراسي; Anxiété aux examens, réussite scolaire; Exam anxiety, academic achievement